The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1751-7915.13698
|View full text |Cite
|
Sign up to set email alerts
|

Potential of laser‐induced fluorescence‐light detection and ranging for future stand‐off virus surveillance

Abstract: Viruses remain a significant public health concern worldwide. Recently, humanity has faced deadly viral infections, including Zika, Ebola and the current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The threat is associated with the ability of the viruses to mutate frequently and adapt to different hosts. Thus, there is the need for robust detection and classification of emerging virus strains to ensure that humanity is prepared in terms of vaccine and drug developments. A point or stand-off b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…LiDAR systems are used to identify and characterize biogenic materials, for example, pathogenic bacteria in both laboratory and field environments [22]. A study of the Laser-induced fluorescence-light detection and ranging (LIF-LiDAR) technique has shown that it can be used for detection, real-time monitoring, and classification of viruses in various environments [23]. A significant benefit of the LIF-LiDAR is the long-range detection of dangerous bio-aerosols, particularly those classified as biological weapons.…”
Section: Lasers Diagnosis Of Virusesmentioning
confidence: 99%
“…LiDAR systems are used to identify and characterize biogenic materials, for example, pathogenic bacteria in both laboratory and field environments [22]. A study of the Laser-induced fluorescence-light detection and ranging (LIF-LiDAR) technique has shown that it can be used for detection, real-time monitoring, and classification of viruses in various environments [23]. A significant benefit of the LIF-LiDAR is the long-range detection of dangerous bio-aerosols, particularly those classified as biological weapons.…”
Section: Lasers Diagnosis Of Virusesmentioning
confidence: 99%
“…Although a number of studies have focused on green synthesis of AgNPs for various applications, particularly antibacterial activities, little information is found on antiviral activities and other properties. At present, considering that microbial pathogens such as viruses are also a major public health concern [ 28 ], the development of coating materials for the inhibition of microorganism growth could be a new and effective approach to prevent bacterial and viral infection [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While E. coli remains a robust indicator of fecal contamination, fluorescence is providing alternative approaches to monitoring which are not just limited to E. coli and BOD as considered in this review. The potential to use fluorescence for virus monitoring has yet to be explored in detail, although there has been some exploratory work in this area (Alimova et al, 2007; Owoicho et al, 2021).…”
Section: Realizing the Potential Of Sensor‐based Technology: Ways For...mentioning
confidence: 99%